Aplikasi Info Pariwisata Kabupaten Solok Selatan Berbasis Android - Vivi Hasti Mayanti; Hidra Amnur; Humaira Humaira; Dwiny Meidelfi (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Solok Selatan Regency is a Regency in the eastern part of the province of West Sumatra. In the County many interesting attractions to visit. As nature tourism, cultural tourism, historical tourism, culinary tourism, and lodging. There has been no use of the android technology to publish existing tourism in Solok Selatan Regency, so information on tourism objects do not meet the attraction of tourists. Tourism android-based applications are used to facilitate tourists in exposing and searching for tourism information in Solok Selatan District. This application can be used as a medium of information at once media Solok Selatan District tourism promotion. This application using GPS on Smartphones to find out the location of the user application and instructions the way to tourist sites through the Google Map. There is a menu to share sights form images to a variety of social media or tools provided on the smartphone, as well as the rating menu to perform the assessment of the tourism objects in the form of the input value rating.